How to conduct a multiple streams study - Zohlnhöfer, Reimut; Herweg, Nicole; Zahariadis, Nikolaos (Methods of the policy process, 2022)
The Multiple Streams Framework (MSF) is one of the most frequently applied approaches to study the policy process. This chapter aims at providing readers with the means to conduct a reliable MSF study. The question of how MSF hypotheses should be tested and how individual concepts should be operationalized has received hardly any scholarly attention. According to the MSF, the problem stream consists of all conditions that policy-makers or people around them perceive as problematic. To capture policy-makers’ attention, conditions must become known to them. According to MSF thinking, this happens via one or a combination of the following attention generating mechanisms: indicators, focusing events, and feedback. When analyzing the policy stream, researchers must identify the relevant policy community, its members and structure, the ideas it generates, and the softening-up process these ideas must survive.